A blockchain-enabled IoT auditing management system complying with ISO/IEC 15408-2. (April 2023) - Cha, Shi-Cho; Meng, Weizhi; Li, Wen-Wei; Yeh, Kuo-Hui
Abstract: Recently, blockchain has attracted attention as one of the most promising key platform technologies for leveraging IoT (Internet of Things) security and auditing management with trusted and decentralized architecture. Therefore, the possibilities of using blockchain for providing scalable management, efficient access, and accountability for the massive numbers of extant and emerging IoT devices merits investigation. In this study, we implement a blockchain-enabled IoT auditing management system complying with ISO/IEC 15408-2 requirements. The implemented system is operated with a stable data retrieval time, i.e. 25.74 to 26.77 microseconds, and a stable compressing and uploading time, i.e. 32.51 and 39.9 microseconds when handling and accessing below 100 logs. With more logs, the processing time raises in a proportional manner. The introduced auditing system represents an evolutionary paradigm not only possessing the advantageous characteristics of blockchain technology, i.e. de-centralization, robustness and tamper-resistance, but also fulfilling the critical requirements from ISO/IEC 15408-2 with respect to auditing perspective. Moreover, the scalability is guaranteed, as our proposed IoT auditing management system is suitable for versatile IoT-oriented application services (even on heterogeneous platforms). Highlights: A novel system architecture complying with concepts including Blockchain, IoT auditing management and ISO/IEC 15408-2. Implementation guidelines of how to integrate blockchain technology and ISO/IEC 15408-2 standards. Proof of concept of an ISO/IEC 15408-2 compliant blockchain system for IoT auditing management. Extension of the ISO/IEC 15408-2 compliant IoT-blockchain system with respective to GDPR and ISO/IEC 29100:2011.